Improving Education of Managers in Construction Sector with the Use of EU Funds. (2016) - Pasławski, Jerzy; Nowotarski, Piotr; Milwicz, Roman; Dubas, Sebastian
Abstract: The need for modernization of curriculum is growing with the development of new technologies and changing construction market all over the world. European Commission has put much effort and funds to European projects connected with education of future managers. Those funds enabled to alter competence of working managers to changing construction industry. Article presents how EU funds influence construction studies and managerial competence at Faculty of Civil and Environmental Engineering at one of the biggest Universities in Poland – Poznan University of Technology. Results of two finished EU Programs are presented, first connected with launching Construction Technology Management, a new course on 2nd cycle studies, and second related to preparation of postgraduate MBA studies in construction, project focused on the joint creation of study and later its implementation within project consortium. In addition, two projects at the stage of application are described. Article reveals how accomplished projects influenced faculty, university, involved workers and graduates of new course conducted in foreign language After presented discussion authors came to the conclusions that programs implemented at Poznan University of Technology, funded by the European Union, helped university to increase offer for current and future students. In addition, these projects, aimed at strengthening cooperation with the industry and helped graduates finding jobs. This provided unique benefits for people who had opportunity to participate in those projects. As another benefit was expanding teaching offer with an MBA studies in the field of construction, in consequence the potential of the didactic units increased significantly. In addition, employees of the institute and the faculty involved in preparation and implementation of those projects, had the opportunity to make new contacts in Europe and worldwide, which positively affected potential of research and teaching, creating new opportunities for development and joint projects.